Traditional sex norms and the innovative function of afternoon dancing - Haavio-Mannila, Elina; Snicker, Raija (Reprint / University of Helsinki, Department of Sociology, 1984)
Summary (s. 243-244).
Keywords: roolit; sukupuoli